Usability and appropriations of ICT’s among university students of the Faculty of Communication Sciences and Techniques of the Universidad Veracruzana - Cano González, Mariedna (Emerging Trends in Education, 2022)
Over the years and technological progress, many aspects have emerged in various areas of daily life, education being a sector of constant updating, it is then that ICTs have become a fundamental piece for new teaching practices and Learning; Higher education, capable of improvement and avant-garde, integrates ICTs in these processes, so the research sought to know how students perceive them as part of their training, how much functionality they manage to distinguish, usability (commissioned of arguing how useful software, a processor, etc.) can be) that university students grant by being active users of the wide options and technological tools that they currently have according to their appropriations or perceptions, for which applied a mixed approach, resulting in the degree of usability that students give to the use of ICT is very high, 98.3%. Keywords: ICT; Usability; Learning; Mediation; Technology tools